Unravelling the molecular players at the cholinergic efferent synapse of the zebrafish lateral line - Carpaneto Freixas, Agustín Eduardo (2020)
The lateral line (LL) is a sensory system that allows fish and amphibians to detect water currents. LL responsiveness is modulated by efferent neurons which aid to distinguish between external and self-generated stimuli, maintaining sensitivity to relevant cues. One component of the efferent system is cholinergic, the activation of which inhibits afferent activity. LL hair cells (HC) share structural, functional and molecular similarities with those of the cochlea, making them a popular model for studying human hearing and balance disorders. Due to these commonalities, one could propose that the receptor at the LL efferent synapse is a α9α10 nicotinic cholinergic one (nAChR). However, the identities of the molecular players underlying acetylcholine (ACh)-mediated inhibition in the LL remain unknown. Surprisingly, through the analysis of single-cell expression studies and in situ hybridization, we describe that α9, but not α10 subunits, are enriched in zebrafish HC. Moreover, the heterologous expression of zebrafish α9 subunits indicates that homomeric receptors are functional and exhibit robust ACh-gated currents blocked by α-Bungarotoxin and strychnine. In addition, in vivo Ca2+ imaging on mechanically-stimulated zebrafish LL HC show that ACh elicits a decrease in evoked Ca2+ signals, irrespective of HC polarity. This effect is blocked by both α-Bungarotoxin and apamin, indicating coupling of ACh-mediated effects to SK potassium channels. Our results indicate that an α9-containing (α9*) nAChR operates at the zebrafish LL efferent synapse. Moreover, the activation of α9* nAChRs most likely leads to LL HC hyperpolarization served by the activation of Ca2+-dependent SK potassium channels.